Evolution of Military Aerial Imagery 1859-2015: From Balloon to Drones - Marco Belogi; Elena Leoni (Nuova Antologia Militare, 2022)
Aerial photography for military purposes started around 1880, when all major European armies used balloons as observation platforms. Starting from the first shot in 1911, the airplane gradually became the main photographic platform through all WWI to take both oblique and vertical aerial shots of front lines. The years 1919-1939 saw the development of topographic mapping from aerial photos, which led all colonial powers to map their areas of influence and to carry out “secret” aero-photographic missions. During WWII, all nations created specific air photographic planes for detecting targets, preparing attack missions and assessing damage, solving huge problems of altitude and autonomy and organizing dedicated photographic units. The Cold War led to the development of recce jet planes, where panchromatic, infrared and radar imagery sensors were installed on the nose of the aircraft. USA also developed strategic air photo collection systems including the U-2 and SR-71 “Blackbird”. The years 1959-1970 saw also the development of satellite photography: CIA’s Corona Project laid the foundation for intelligence satellite imagery. Between the 1970s and 2000s, new digital electro-optical or radar sensors for satellites with increasing resolution were developed both for military and civilian use. In parallel, unmanned Aerial Vehicles can take and send oblique motion video, while others can carry out systematic vertical footage of the terrain, such as the Buckeye system in Iraq and Afghanistan. From old balloon photographs to recent Buckeye imagery, an important secondary use of this military technology has been the opportunity to better study archaeological and monumental sites.